Determination of Antioxidative and ACE-inhibitory Activities from Red Tilapia Protein Hydrolysates Generated by Alcalase and Thermolysin - Nur ‘Aliah Daud; Abdul Salam Babji; Salma Mohamad Yusop (Current Advances in Chemistry and Biochemistry Vol. 4, 2021)
Production of fish protein hydrolysates has been widely studied in order to explore the potential of fish protein and industrial potential of fish wastes as functional bioactive peptides. In this research, the activities of antioxidative and angiotensin converting enzyme (ACE)-inhibitory peptides derived from freshwater fish of Red Tilapia protein (Oreochromis niloticus) using alcalase and thermolysin enzymes were evaluated. The enzymatic hydrolysis process was performed for 4 hours at 37°C, pH 7.4. After two hours of hydrolysis with thermolysin and alcalase enzymes resulted in degree of hydrolysis of 76.29% and 63.49%, respectively. Hydrolysates obtained after 1 hour and 2 hours hydrolysis were chosen for further study on the bioactive activities. The result showed that the thermolysin enzyme yielded higher antioxidant activities than alcalase enzyme based on ABTS radical scavenging activity and reducing power assays. For ACE-inhibitory assay, thermolysin enzyme yielded higher ACE-inhibitory activities after 1 hour hydrolysis while alcalase enzyme yielded higher inhibition activities after 2 hours hydrolysis. Chosen cut-off interval of hydrolysates showed that the thermolysin hydrolysates have strong inhibition effects towards ACE enzyme than alcalase hydrolysates. This study had demonstrated that the hydrolysates produced from Red Tilapia protein may contribute as a health promoting ingredient, to reduce free radical in human system as well as improving the shelf-life of functional food products. The hydrolysates may also be used as an ingredient which have the antihypertensive effects towards the mild hypertension patients.